1999
DOI: 10.1002/(sici)1098-1071(1999)10:1<79::aid-hc14>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

1,3-cycloadditions of pyridinium N-arylimides

Abstract: The title compounds (5a: Ar = C6H5, 5b: Ar = 2‐pyridyl) are 1,3‐dipoles of the azomethine imine type; their 1,3‐cycloadditions are accompanied by the loss of the pyridinium resonance energy. As a consequence, the interaction with electron‐deficient ethylenes gives rise to cycloaddition/cycloreversion equilibria, in contrast to the cycloadditions of isoquinolinium N‐arylimides; enamines do not react with 5. The cycloadducts of 5a to dimethyl maleate, fumaronitrile, and acrylonitrile are Nβ‐dienyl‐phenylhydrazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recently, Huisgen et al have investigated this reaction. Remarkably, these authors have found that the reaction of 12a with fumaronitrile at room temperature gives risevia the cycloaddition routeto a bridged ring system 13a (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Huisgen et al have investigated this reaction. Remarkably, these authors have found that the reaction of 12a with fumaronitrile at room temperature gives risevia the cycloaddition routeto a bridged ring system 13a (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Closely related to maleate adduct 11 is 42, which is the major regioisomer in the cycloaddition of 2 to methyl cis-3-cyanoacrylate [4]; it is the 1a-CO 2 Me group of 11 Table 2). We reported recently on the cycloaddition of pyridinium N-phenylimide with dimethyl maleate; adduct 51 smoothly underwent the hydrazo rearrangement to give a tetracyclic aminal [29]. In the framework of structure 49b, removal of the fused benzo ring reduces steric hindrance and allows the [3,3]-sigmatropic shift to proceed.…”
mentioning
confidence: 99%